2011
DOI: 10.1179/1743285510y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of wüstite prepared from Baharia iron ore sinter during reduction with CO–CO2–N2gas mixture

Abstract: Two wu ¨stite samples were prepared from reagent grade hematite and Baharia iron ore sinter by a gaseous reduction with 50%CO-CO 2 gas mixture at 1273 K. Both wu ¨stite samples were isothermally reduced at 1173-1373 K by different ratios of CO/CO 2 /N 2 which closely represent the coke gases in the blast furnace. The influences of temperature and gas composition on the reduction behaviour and the morphology were investigated. The reduction rate of both wu ¨stite samples increased gradually with increasing reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Bahgat studied the behaviour of wustite prepared from Baharia iron ore sinter during reduction with CO-CO 2 -N 2 gas mixture. These results showed the reduction rate of pure wustite samples that was most likely controlled by the combined effect of chemical reaction and gaseous diffusion mechanisms while the reduction rate of wustite from iron ore sinter was most likely controlled by interfacial chemical reaction mechanism (Bahgat et al, 2011). Therefore, the gas-solid reaction of nickel laterite ore was controlled by interfacial chemical reaction, and the reaction rate was determined by the chemical reaction rate.…”
Section: Reduction Mechanism Analysismentioning
confidence: 86%
“…Bahgat studied the behaviour of wustite prepared from Baharia iron ore sinter during reduction with CO-CO 2 -N 2 gas mixture. These results showed the reduction rate of pure wustite samples that was most likely controlled by the combined effect of chemical reaction and gaseous diffusion mechanisms while the reduction rate of wustite from iron ore sinter was most likely controlled by interfacial chemical reaction mechanism (Bahgat et al, 2011). Therefore, the gas-solid reaction of nickel laterite ore was controlled by interfacial chemical reaction, and the reaction rate was determined by the chemical reaction rate.…”
Section: Reduction Mechanism Analysismentioning
confidence: 86%
“…As mentioned previously,18, 19 the total reduction process in BF lasts for 120 min, but the reduction status at 90 min attracted more attention because it is the time needed for the burden to pass through the temperature region of 900–1100°C in BF. From the isothermal reduction curves of pure wüstite, it was found that at 900–1100°C, comparatively, the reduction extent was clearly enhanced as it mainly reached 100% after 40–90 min while the reduction extent after 90 min was in the range of 50–75 or 81–99·5% for samples isothermally reduced with CO/CO 2 /N 2 (coke gases) or H 2 /CO/CO 2 /N 2 (low natural gases injection with low oxygen enrichment) respectively 20,21…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, from isothermal reduction curves, it was found that the reduction extent after 90 min was in the range of 70-80%, which is relatively higher compared with the wu ¨stite from iron ore sinter reduced with CO/CO 2 /N 2 (34-48%) or with H 2 /CO/CO 2 /N 2 (54-69%). 20,21 Enhancement of wu ¨stite reducibility at 900-1100uC decreases the remaining quantity of unreduced wu ¨stite, which descends to the high temperature region in BF. This will consequently lead to the reduction in coke consumption and CO 2 emission.…”
Section: Samples From Iron Ore Sintermentioning
confidence: 99%
See 1 more Smart Citation
“…The behavior of wustite prepared from Baharia iron ore sinter during reduction with different ratios of CO-CO 2 -N 2 gas mixture at 800 -1100ºC was investigated 10 . The influence of temperature and gas composition on the reduction behaviour and the morphology was investigated.…”
Section: Reduction Of Iron Oresmentioning
confidence: 99%